Limits of responsibility of subjects of international law for the use of weapons of mass destruction in outer space - Leś, Jakub (Uniwersytet Wrocławski Koło Doktryn Politycznych i Prawnych, 2023)
In the long history of space exploration, we could witness a creation of multiple treaties and principles covering the responsibility of states and other parties of international law for the use of weapons of mass destruction in outer space. Comprising a range of potential usage of weapons of mass destruction on the Earth’s orbits, moon and other celestial bodies, they present a vague range of boundaries under which parties might be held accountable for their actions in outer space. The paper presents a perspective on possible limitations of responsibility of subjects of international law for the use of weapons of mass destruction in outer space by providing the legal analysis of the topic with due regard to historical records and currently available data. Paper is placed in context of previous work of scholars in the respective fields.
Keywords: limits of responsibility; weapons of mass destruction; outer space; low earth orbit